Effect of starter culture on staphylococcal enterotoxin and thermonuclease production in dry sausage. - Niskanen, A (1976)
Different amounts of enterotoxin A-, B-, and C1-producing staphylococci were added to dry sausage prepared by normal processes, either alone or in conjunction with a starter culture (micrococci and lactobacilli). The sausage was examined after 0, 3, 7, 14, and 30 days for staphylococci, micrococci, and lactobacilli, and measurements were made of water activity, pH, enterotoxin, and thermostable nuclease. The results showed that in the absence of starter culture measurable amounts of enterotoxin A were formed in a 200-g sample of dry sausage in 3 days, the level of Staphylococcus aureus infection being over 10(6) cells/g. Enterotoxin B was not found, although the total number of staphylococci was over 10(8) cells/g. Enterotoxin C1 was observed when the Staphylococcus count was about 8 X 10(7) cells/g, but was no longer detectable after 7 days. The starter culture prevented the production of enterotoxin A in all cases investigated. By contrast, a very high-level inoculation of an enterotoxin C1-producing strain gave a positive result after 3 days of incubation even in the presence of a starter culture. Heat-stable nuclease was observed in all sausages to which enterotoxin-producing staphylococci were added. The cell count determined in a sample of sausage had no definite correlation with the thermonuclease activity of the sample.